Pengaruh Video Animasi Pendidikan Gizi Terhadap Pengetahuan dan Asupan Gizi Pada Anak SMP - Dinatha, Ngurah Mahendra; Sariyani, Made Dewi; Bhala, Maria Regina (Lontara Journal of Health Science and Technology, 2024)
High school students still lack knowledge of nutrition issues, so it is necessary to carry out nutrition education with the help of animated video media to attract the attention and motivation of students to learn and apply it. The purpose of this research is to investigate the influence of video animation of nutritional education on knowledge and nutrition intake in high school students. This research is a Pre-Experimental study with a One Group pretest and posttest design. The population in this study is the entire students of the junior high school Citra Bakti of 75 people, with a sample of 34 people selected based on sampling purposive Method of data collection of knowledge with filling questionnaire and data of energy, protein and iron intake with the method of recall 2x24 hours. The results of the study show that there is a significant influence on knowledge, energy intake, proyein and otherwise no effect on consumption of iron